IDENTIFIKASI SENYAWA FLAVONOID PADA FRAKSI N-BUTANOL BUNGA BUGENVIL UNGU (Bougenvillea spectabilis) DENGAN SPEKTROFOTOMETER UV-VIS - Yulianis Yulianis; Sangra Maysenta; Siti Hamidatul Aliyah (JURNAL BIOSENSE, 2023)
Bougainvillea purple flowers (bougenvillea spectabilis) is a plant that contains secondary metabolites one of them flavonoids. This study aims to identify the type of flavonoids in the purple bougenville blend n-butanol. The identification of the bougainvillea n-butanol fraction was performed by separation method using preparative TLC by using eluent nbutanol: acetic acid: water (4: 1: 5) in 3 stains with Rf 0.2, Rf 0.3, and Rf 0, 6 in a shear reagent at Rf 0.2 in flavonoid guessing using UV-Vis spectrophotometry, based on analysis using UV-Vis spectrophotometer has absorption at wavelength 372 band 1 and 276 band 2 then flavonoid flavonoids are expected. The results of this study showed that the fraction of purple bougainvillea flowers contain flavonoid flavonoids. Conclusion From this study Based on thin layer chromatography and UV-Vis spectrum analysis with shear compound reagents in bougainvillea flower is thought to contain flavonoid flavonoids. Keywords: purple bougainvillea; bougenvillea spectabilis; flavonoid; flavonol.